2009
DOI: 10.1590/s1517-83822009000300030
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa KUCd1, a possible candidate for cadmium bioremediation

Abstract: A cadmium (8 mM) resistant Pseudomonas aeruginosa strain KUCd1 exhibiting high Cd accumulation under in vitro aerobic condition has been reported. The isolate showed a significant ability to remove more than 75% and 89% of the soluble cadmium during the active growth phase from the growth medium and from Cd-amended industrial wastewater under growth supportive condition. Transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDXS) suggest the presence of Cd in the cells from mid-stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 13 publications
4
29
0
Order By: Relevance
“…Bacteria employ various mechanisms to survive in stress environments, like detoxification, efflux mechanisms, adsorption, and compartmentalization . Cd uptake by Pseudomonas species has also been studied earlier . Our findings with dead cells of P. putida mt2 are also in agreement with those of Kurek et al .…”
Section: Discussionsupporting
confidence: 92%
“…Bacteria employ various mechanisms to survive in stress environments, like detoxification, efflux mechanisms, adsorption, and compartmentalization . Cd uptake by Pseudomonas species has also been studied earlier . Our findings with dead cells of P. putida mt2 are also in agreement with those of Kurek et al .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, many investigators have reported the bioaccumulation of cadmium onto natural microbial populations like bacteria and algae as the new bioremediation technology [9,10]. The microbes use various survival strategies to combat the cadmium stress that include metal ions sequestration, active efflux of metals; some use enzymatic detoxification and cadmium accumulation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The approach suffers from the fact that in the presence of cadmium, sulfate reduction rate gets reduced (Pagnanelli et al 2010). Bioaccumulation of cadmium by a cadmium-resistant Pseudomonas aeruginosa strain KUCd1 was also reported by Sinha and Mukherjee (2009) at pH 8.5, under strict aerobic conditions as well as continuous supply of nutrients. On the other hand, precipitation of cadmium as cadmium sulfide via hydrogen sulfide generation under completely anaerobic conditions in Pseudomonas aeruginosa, Salmonella typhimurium, and Treponema denticola has been reported by several authors (Wang et al 1997(Wang et al , 2000(Wang et al , 2001White and Gadd 1996;Bang et al 2000).…”
Section: Bioprecipitation Of Metal Ions From Single-ion Solutionsmentioning
confidence: 63%